EKOTEOLOGI DALAM AKSI: MEMBANGUN KESADARAN DAN PRAKTEK EKOLOGI BERBASIS NILAI-NILAI KEKRISTENAN - Ratna Saragih; Rogate Artha Gultom; Dapot Damanik (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service Program (PkM) aims to enhance the ecological awareness and understanding of the residents of Bahal Batu 1 Village, Siborongborong District, North Tapanuli Regency, through an ecotheological approach grounded in Christian values. This program was implemented as part of the University’s Tri Dharma mandate in addressing various environmental issues faced by the community, including inadequate waste management practices, the habit of open waste burning, the excessive use of agricultural chemicals, and a low level of awareness regarding environmental conservation. The method employed was Participatory Action Research (PAR), consisting of several stages, including preparation, needs assessment, program implementation, and community mentoring. The activities were carried out through educational outreach, participatory discussions, biblical reflection, and environmental education on waste management, water resource conservation, reforestation, and environmentally friendly agricultural practices. The results of the program indicated an increase in the community’s understanding of the relationship between the Christian faith and the responsibility to care for the environment as an expression of lived faith. Community members began to recognize that environmental conservation is not merely a social responsibility, but also a moral and spiritual obligation as part of their stewardship of God's creation.